التحسين والتقبيح العقليان واثرهما في بعض مسائل أصول الفقه بين الاشاعرة والمعتزلة - حدد, يوسف; تجاني, محمدالعيد; غربي, نجيب (University of Eloued-جامعة الوادي, 2018)
إن علم أصول الفقه يستمد من عدة علوم أخرى، من بينها علم الكلام، وفي هذه المذكرة نسلط الضوء على علاقة علم أصول الفقه بعلم الكلام من خلال أثر جزئية كلامية على بعض مسائل علم اصول الفقه، وهي التحسين والتقبيح العقليين وأثر الاختلاف فيها في مسائل الحكم الشرعي، حيث أن الأشاعرة نفوا أن يحسن العقل أو يقبح بينما أثبت المعتزلة التحسين والتقبيح للعقل. ونتيجة لهذا الاختلاف بين الأشاعرة والمعتزلة، اختلفت آراؤهم في مسائل الحكم الشرعي من الحاكم والحكم والمحكوم عليه والمحكوم فيه، فكل رأي يتوافق مع التحسين والتقبيح العقليين تبناه المعت زلة ، وكل رأي يتناقض مع التحسين والتقبيح العقليين تبناه الأشاعرة. Abstract The science of Principles of Fiqh derives from several other sciences, including the science of speech, In this note, we highlight the relationship between the science of Principles of Fiqh and the science of speech Through a speech partial effect on some of the issues of Principles of Fiqh, namely, the optimization and making bad by mind and the impact of difference in them in matters of legitimate governance, where the Achaira rejected this thing and the Motazila accepted this thing. As a result of this difference between Achaira and Motazila, their opinions differed in matters of legitimate governance, every opinion corresponds to the optimization and making bad by mind adopted by the Motazila, and Every opinion contradicts with the optimization and making bad by mind adopted by the Achaira.
مذكرة ليسانس
Keywords: التحسين /التقبيح / مسائل / أصول الفقه /الاشاعرة /المعتزلة; Amélioration / laideur / enjeux / principes de jurisprudence / Ash’ari / Mu’tazila